Peer Support as a Strategic Lever for Addressing Indonesia's Higher Education Completion Crisis - Qolbi, Hanifah Qonita Mutmainnatul; Mirawati, Ira; El Karimah, Kismiyati (Education and Development Research, 2026)
Indonesia faces a critical higher education completion crisis, with only 28.7% of students graduating on time, a stark contrast to the OECD average of 68%. This challenge is intensified by a recent policy reducing the maximum study period to five years. While institutional responses have predominantly focused on top-down, resource-intensive infrastructure, a fundamental resource remains critically underutilized: structured peer support. This commentary argues that peer support is not a peripheral activity but a central, cost-effective strategic lever for improving graduation rates. Grounded in House's (1981) Social Support Theory and informed by contemporary evidence from educational psychology, neurobiology, and digital culture, this paper bridges global best practices with the Indonesian context. Critically, we identify a specific gap in the literature: while the efficacy of peer support is globally recognized, there is a lack of a culturally-adapted framework that systematically integrates Indonesia's collectivist values (gotong royong) with the digitally-native behaviors of Gen Z students. By analyzing the four dimensions of missing support emotional, instrumental, informational, and appraisal this article highlights the unique alignment between peer support mechanisms and Indonesia's socio-cultural landscape. It concludes with actionable policy recommendations for institutions, national policymakers, and student organizations to leverage this scalable solution to transform the nation's higher education landscape.